The M1 and NP proteins of influenza A virus form homo- but not heterooligomeric complexes when coexpressed in BHK-21 cells. - Zhao, Hongxing; Ekström, Maria; Garoff, Henrik (Journal of General Virology, 1998)
The nucleoprotein (NP) and matrix protein (M1) are the most abundant structural proteins of influenza A virus. M1 forms a protein layer beneath the viral envelope and NP constitutes the protein backbone of the ribonucleoproteins (RNPs). In order to elucidate the functions of these proteins in virus assembly we have expressed NP and M1 in BHK-21 cells using Semliki Forest virus replicons and analysed their molecular interactions. We found that both M1 and NP engaged in extensive homooligomerization reactions soon after synthesis. However, there was no detectable heterooligomerization taking place between the two viral proteins, nor between these and host proteins. One interpreta-tion of these results is that homooligomers, and not monomers, of NP and M1 are used as building blocks during RNP assembly and formation of the submembranous M1 layer, respectively. The complete absence of M1-NP heterooligomers suggests, on the other hand, that these two major viral proteins do not interact directly with each other during virus assembly. We also found that a fraction of M1 associated with cellular membranes. This did not, however, result in membrane budding or vesicularization as was the case with the matrix protein of vesicular stomatitis virus when expressed separately (P. A. Justice and others, Journal of Virology 69, 3156– 3160, 1995).